An analytical model for the transverse permeability of gas diffusion layer with electrical double layer effects in proton exchange membrane fuel cells. (13th September 2018) - Liang, Mingchao; Liu, Yaming; Xiao, Boqi; Yang, Shanshan; Wang, Zhankui; Han, Hongmei
Abstract: An analytical model is presented for the transverse permeability of gas diffusion layer (GDL) based on an ordered array of parallel charged circular cylinders at the steady state. The formula of calculating the permeability of the transverse direction is given by solving the fluid momentum equation in a unit cell. In the present approach, the proposed model is explicitly related to the porosity and fiber radius of fibrous porous media, the zeta potential, and the physical properties of the electrolyte solution. Besides, the effects of these parameters (the porosity, unit cell aspect ratio, fiber radius, and molar concentration) on the transverse permeability are discussed detailedly. The model predictions are compared with the previous studies in the available literature, and good agreement is found. Highlights: A model is built for the transverse permeability in fuel cell porous media. The effects of electrical double layer are discussed and analyzed. Model predictions are in good agreement with the previous data.